2018
DOI: 10.3389/fphys.2018.00380
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Candidate Iron Transporters From the ZIP/ZnT Gene Families in the Mosquito Aedes aegypti

Abstract: Mosquito-transmitted viral pathogens, such as dengue and Zika, afflict tens of thousands of people every year. These viruses are transmitted during the blood-feeding process that is required for mosquito reproduction, the most important vector being Aedes aegypti. While vertebrate blood is rich in protein, its high iron content is potentially toxic to mosquitoes. Although iron transport and sequestration are essential in the reproduction of vector mosquitoes, we discovered that culicine mosquitoes lack homolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 39 publications
3
23
0
Order By: Relevance
“…The functions of some of these 22 shared genes include 3 ABC transporters, 1 member of the ZIP family of zinc transporters (AAEL014762) and 1 cystinosin (AAEL006113) and 7 of unknown function. AAEL014762 is an iron transporter localized in the endocytic vesicles and is important in exporting iron from the midgut [ 31 , 32 ]. Cystinosin is involved in the transport of cystine into the cytosol which then serves as a site for redox reactions to occur, indicating its important role in heme-generated ROS mitigation.…”
Section: Resultsmentioning
confidence: 99%
“…The functions of some of these 22 shared genes include 3 ABC transporters, 1 member of the ZIP family of zinc transporters (AAEL014762) and 1 cystinosin (AAEL006113) and 7 of unknown function. AAEL014762 is an iron transporter localized in the endocytic vesicles and is important in exporting iron from the midgut [ 31 , 32 ]. Cystinosin is involved in the transport of cystine into the cytosol which then serves as a site for redox reactions to occur, indicating its important role in heme-generated ROS mitigation.…”
Section: Resultsmentioning
confidence: 99%
“…It is probable that iron deposition and recovery from ferritin for use in various cellular and growth process involves chaperone proteins (Philpott and Jadhav 2019). Proteins that could serve as iron transporters in mosquitoes that are expressed in ovaries (Tsujimoto et al 2018) and Malpighian tubules (Martinez-Barnetche et al 2007) have recently been identified.…”
Section: Discussionmentioning
confidence: 99%
“…Available evidence also supports that in insects the ferritin subunits are synthesized in the endoplasmic reticulum and separately targeted to different Golgi-like vesicles (HCH) or other vesicles (LCH) that with time following iron stimulation assemble to form the functional ferritin molecules (Nichol and Locke 1990, Locke et al 1991, Rosas-Arellano et al 2016) Both HCH and LCH subunits are required for functional particle formation. Iron loading occurs only with the assembled particle inside the Golgi-like vesicles and zinc-regulated and iron-regulated transporter 13 (Zip13) imports iron into the vesicles (Xiao et al 2014, Rosas-Arellano et al 2016, Tsujimoto et al 2018). Iron-loaded ferritin is retained in a separate Golgi compartment in cells or secreted (Geiser et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…In particular, silencing of AaeZIP13 showed increased iron accumulation in the midgut and reduced iron in the ovaries at 24 h post bloodmeal as expected from the results for dZIP13 in D. melanogaster. However, the effect did not persist, as once egg maturation was complete we observed no difference in fecundity and fertility [20].…”
Section: Introductionmentioning
confidence: 61%
“…A separate plasmid containing the Ae. aegypti ferritin light chain (AAEL007383) promoter-firefly luciferase (FerLCH-FFL) [20] gene was linearized 3' of the FFL ORF using PshAI and treated with shrimp alkaline phosphatase (NEB). The PUb-RL fragment was ligated into the linearized pGL3-LCH-FFL, and only tail-to-tail orientation constructs were sequenced to confirm the direction and integrity of the insert.…”
Section: Dual-luciferase Plasmid Constructionmentioning
confidence: 99%